1998
DOI: 10.1590/s0103-50531998000200010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of B-DNA Minor-Groove Binders: The Rigid Analogue Approach to Synthesise Antileishmaniasis Compounds: A Molecular Modeling Study

Abstract: RI DFWLRQ LV QRW NQRZQ EXW LW KDV EHHQ VXJJHVWHG WKDW WKH\ ELQG WR % '1$ PLQRU JURRYHV :LWKLQ WKH GUXJ GHVLJQ EDVHG XSRQ WKH UHFHSWRU VWUXFWXUH ZH VKRZ WKH ELQGLQJ HQHUJLHV IRU VRPH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Earlier molecular modeling studies with a 12mer DNA duplex, carried out on 35 and on pentamidine 7, showed preferential binding to AATT sequence [80]. The G-NH 2 group in minor groove sequences with GC base pairs sterically interferes with strong minor groove complex formation.…”
Section: Dockingmentioning
confidence: 94%
“…Earlier molecular modeling studies with a 12mer DNA duplex, carried out on 35 and on pentamidine 7, showed preferential binding to AATT sequence [80]. The G-NH 2 group in minor groove sequences with GC base pairs sterically interferes with strong minor groove complex formation.…”
Section: Dockingmentioning
confidence: 94%
“…Portanto, não se trata de uma busca exaustiva. Apenas por brevidade inerente, as palavras escolhidas foram: QUÍMICA MEDICINAL [13][14][15][16][17][18][19][20][21][22] , QSAR 14, 23-62 e PLANEJAMENTO DE FÁRMACOS 14,18,21,44,45,56,57,59,[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] .…”
Section: Cenário Científico E Tecnológico No País Depois De 1991unclassified
“…25 Estudos prévios de modelagem molecular e relação estrutura-atividade utilizando compostos amidínicos têm mostrado a importância da estrutura isoélica e da carga positiva presente nestes compostos para a interação com a fenda menor do B-DNA. 18,[26][27][28] Estudos de modelagem molecular sugerem ainda que o grupo amidínico desses compostos forme ligações de hidrogênio com os átomos receptores das bases A-T presentes na fenda menor. 17,22,26 Há fortes evidências de que eles levariam à subsequente inibição de enzimas DNA-dependentes.…”
Section: Introductionunclassified